2010
DOI: 10.1177/0738894209343979
|View full text |Cite
|
Sign up to set email alerts
|

Legal Systems and Peaceful Attempts to Resolve Territorial Disputes

Abstract: This paper focuses on how domestic legal systems influence states’ choices of peaceful dispute resolution methods. In order to increase familiarity with rules of peaceful resolution of disputes, states use their domestic legal systems to provide them with clues about the most trustworthy ways to settle disputes. States tend to choose methods of dispute resolution that are similar to those embedded in their domestic legal systems. Empirical analyses support the conjecture of a linkage between domestic law and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
0
26
1
1
Order By: Relevance
“…As similar processes for adjudicating disputes should inform the ability of mediators to identify processes that are familiar (and acceptable) to the disputants, we identify whether the mediating state and the civil war state both rely on common law, civil law, Islamic law, or mixed legal systems. 5 These data are drawn from the Powell and Wiegand (2010) dataset. Domestic legal system refers to the type of legal system practised by a state in its constitution, laws, and judicial system, comprising civil, common, Islamic, and mixed legal systems (Mitchell and Powell, 2011; Powell and Wiegand, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As similar processes for adjudicating disputes should inform the ability of mediators to identify processes that are familiar (and acceptable) to the disputants, we identify whether the mediating state and the civil war state both rely on common law, civil law, Islamic law, or mixed legal systems. 5 These data are drawn from the Powell and Wiegand (2010) dataset. Domestic legal system refers to the type of legal system practised by a state in its constitution, laws, and judicial system, comprising civil, common, Islamic, and mixed legal systems (Mitchell and Powell, 2011; Powell and Wiegand, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…5 These data are drawn from the Powell and Wiegand (2010) dataset. Domestic legal system refers to the type of legal system practised by a state in its constitution, laws, and judicial system, comprising civil, common, Islamic, and mixed legal systems (Mitchell and Powell, 2011; Powell and Wiegand, 2010). Similarity of a domestic legal system shared between the conflict state and mediator state should help mediators to better understand procedures of justice, reconciliation, and governance norms in the correct context.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Bercovitch and Jackson ( 2001 ) showed that dyads of states that are more unequal in terms of their power and that are involved in more complex disputes are more likely to resolve their disputes through mediation rather than bilateral negotiations. Powell and Wiegand ( 2010 ) also explored the choice of bilateral or thirdparty confl ict management, fi nding that domestic legal traditions predict management method choices. Yet these works do not distinguish between states and IOs as third-party confl ict managers and therefore can off er only partial answers to our question.…”
Section: Theorymentioning
confidence: 99%
“…Proponents of the democratic legalistic perspective assert that democracies are generally more willing to depend on the rule of law in international affairs due to their affinity with certain international legal institutions (Slaughter 1995). Building on the "affinity" argument, several scholars argue that domestic legal system types (civil, common, and Islamic) determine states' attitudes towards international courts (Powell and Wiegand 2010;Mitchell and Powell 2011;Powell 2012). In short, states have incentives to create and join international courts in their own legal image to reduce uncertainty in future bargaining situations.…”
Section: States' Support For International Courts-the Literaturementioning
confidence: 99%